Larvicidal activity of essential oil from Vitex negundo and Vitex trifolia on dengue vector mosquito Aedes aegypti - Trilokesh Chandrasekaran; Aishwarya Thyagarajan; Prabhakaran Ganapathi Santhakumari; Agiesh Kumar Balakrishna Pillai; Uma Maheswari Krishnan (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract INTRODUCTION: The ability of Vitex trifolia and Vitex negundo essential oils to kill Aedes aegypti and Culex quinquefasciatus larvae was evaluated. METHODS: The larvae were treated with their respective essential oils at 50-125 ppm concentration. RESULTS: LC50 and LC90 for V. trifolia against Ae. aegypti and C. quinquefasciatus, and those for V. negundo against Ae. aegypti were 57.7+0.4, 77.9+0.9 ppm and 55.17+3.14, 78.28+2.23 ppm, and 50.86+0.9, 73.12+1.3 ppm, respectively. Eucalyptol and caryophyllene were the major components in Vitex trifolia and Vitex negundo essential oil, respectively. CONCLUSIONS: This study revealed potential larvicidal properties of essential oil from V. trifolia.